2014
DOI: 10.1590/1413-812320141911.13922013
|View full text |Cite
|
Sign up to set email alerts
|

Acesso aos serviços básicos de saúde e fatores associados: estudo de base populacional

Abstract: Acesso aos serviços básicos de saúde e fatores associados: estudo de base populacionalAccess to basic health services and associated factors: a population-based study (OR = 3,224) with accessibility (OR = 0,146) and micro-area of residence (OR = 10,918). These findings suggest that access is related to the impressions created by the care received at the health unit and is based on experiences with the service, but can also be strongly modulated by individual aspects and factors related to the territory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
8
0
8
Order By: Relevance
“…Authors have published these studies between 1999 and 2017 (median: 2009) 5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37 (Table 1). The authors of five studies reported having no conflicts of interest 19,28,31,33,35 , while in the other studies the authors did not disclose whether they had any conflicts of interest, nor did they examine interviewers' biases (in qualitative studies).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors have published these studies between 1999 and 2017 (median: 2009) 5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37 (Table 1). The authors of five studies reported having no conflicts of interest 19,28,31,33,35 , while in the other studies the authors did not disclose whether they had any conflicts of interest, nor did they examine interviewers' biases (in qualitative studies).…”
Section: Resultsmentioning
confidence: 99%
“…While some studies had national coverage 5,12,13,14,22,24,25 , others covered certain geographical regions (e.g., Northeast or Southeast) 8,11,15,20,26 , states 16,33 , metropolitan areas 9,17,18 , municipalities 10,19,21,23,27,28,30,31,34,35,36,37 or parts of a municipality 22,32 . The study population included varied age groups, but most of them showed a balanced gender composition, with the exception of one study about men's health 37 and two about women's health 19,31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data collection instrument used was based on similar population-based studies 15,16 . Specifically, the dimension of access was adapted from the Ministry of Health's Vigitel 2010 survey 17 , and was previously tested in this research project through a pilot study in a specially selected census tract, the data of which were not included in the final survey.…”
Section: Methodsmentioning
confidence: 99%